2022
DOI: 10.1007/s40262-022-01181-8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Pragmatic PBPK Modeling Approach: Towards Model-Informed Dosing in Pediatric Clinical Care

Abstract: Background and Objective More than half of all drugs are still prescribed off-label to children. Pharmacokinetic (PK) data are needed to support off-label dosing, however for many drugs such data are either sparse or not representative. Physiologicallybased pharmacokinetic (PBPK) models are increasingly used to study PK and guide dosing decisions. Building compound models to study PK requires expertise and is time-consuming. Therefore, in this paper, we studied the feasibility of predicting pediatric exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Our study sides with recent critiques of the twofold criterion. van der Heijden et al [ 29 ] argued that more stringent ranges for predicted-to-observed ratios should be considered. Another limitation of the twofold ranges was highlighted by Guest et al [ 30 ] and Abduljalil et al [ 13 ] who demonstrated the necessity of incorporating variability of the PK data into the evaluation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Our study sides with recent critiques of the twofold criterion. van der Heijden et al [ 29 ] argued that more stringent ranges for predicted-to-observed ratios should be considered. Another limitation of the twofold ranges was highlighted by Guest et al [ 30 ] and Abduljalil et al [ 13 ] who demonstrated the necessity of incorporating variability of the PK data into the evaluation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A less time-consuming PBPK modeling approach in which pre-existing compound models are combined with pediatric physiology models can be pragmatic and feasible to predict PK and guide drug dosing in pediatric clinical care. 12,13 Rapid growth of PBPK to support drug development decisions in the last decade resulted in active engagement of major regulators to develop guidelines around the use of this technology. The process is a work in progress.…”
Section: Physiologically-based Pharmacokinetic Modeling For Drug Dosi...mentioning
confidence: 99%
“…We described a pragmatic workflow for pediatric PBPK model verification before, applying it to several drugs. 13 In this approach, a PBPK model is first verified with an adult population to demonstrate adequate predictive performance when predicting PKs in adults before integrating age-related physiological changes to predict PK in pediatrics and subsequently, if relevant, in preterm neonates. Below we describe relevant steps in more detail and we outline how the approach can be applied in three scenarios of decreasing clinical data availability for model verification.…”
Section: Model Verification Workflowmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the field of paediatric pharmacokinetics, the use of pharmacokinetic modelling, particularly physiological-based pharmacokinetics (PBPK), has revolutionised the ability to extrapolate drug pharmacokinetics across age groups, allowing for pragmatic determination of paediatric plasma concentrations to support drug licensing and clinical dosing. This approach relies on the established principles of mechanistic PBPK modelling to describe tissue volumes, tissue perfusion, renal/liver function, blood biochemistry and drug metabolism enzyme/and drug transporter protein expression [ 15 ], in addition to the inclusion of development changes [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%